What Impact Does Participation in a Communication Skills Training Program Have on Health Professionals’ Communication Behaviors: Findings from a Qualitative Study - V. White; M. Chiswell; E. Webber; P. Martin; A. Piper (Journal of Cancer Education, 2023)
Communication skills training can enhance health professionals’ knowledge and repertoire of effective communication practices. This paper describes the conceptual model underlying a 3-day retreat communication skills training program, methods used for training, and participant perception of outcomes from the training using qualitative interviews. Repeated qualitative telephone interviews (approximately 6 months apart) with participants of a 3-day Clinical Consultation Skills Retreat. Fourteen participants (70% response, 57% doctors) took part at Time 1, with 12 participating at Time 2. Semi-structured interviews were recorded and transcribed, and directional content analysis was conducted to assess themes in areas of key learnings, implementation of skills, and barriers. The training was received very positively with participants valuing the small group learning, role play, and facilitator skills. Key learnings were grouped into two themes: (i) tips and strategies to use in clinical practice and (ii) communication frameworks/methods, with the second theme reflecting an awareness of different communication styles. Most participants had tried to implement their new skills, with implementation reported as a more deliberate activity at T1 than at T2. Those implementing the new skills noted more open conversations with patients. Practical barriers of lack of time and expectations of others were mentioned more often at T2. A 3-day retreat-based communication training program was positively received and had a positive impact on the use of new communication skills. While further work is needed to determine whether effects of training are evidenced in objective clinical behaviors, the positive longer-term benefits found suggest this work would be worthwhile.